Disharmony of intra-Islamic religious life at the women's majelis ta'lim in Aceh - Rasyidah, Rasyidah; Husein, Mustabsyirah; Amin, Husna; Dendi, Dwi; Masrizal, Masrizal (Universitas Islam Negeri Ar-Raniry, 2022)
This paper explains the disharmony of intra-Islamic religious life at the women Majelis Ta’lim in Aceh. Majelis Ta’lim as one of the local wisdoms in Aceh which is still practiced as a community school that educates women/mothers in the community. This should be able to become a pillar that strengthens the peaceful role of women. However, this becomes difficult, because of there is disharmony situation in religious interactions in the women's Majelis Ta’lim. Whereas the peaceful energy possessed by women should be maximized to build intra-Islamic religious harmony. This study used a qualitative approach, using data collection techniques through interviews, observations and FGDs. The results of the study showed that there were three issues of disharmony experienced by women in the Majelis Ta’lim. They were 1) the immature attitude in responding to various differences in practice among members of PERTI, NU and Muhammadiyah, 2) the resistance of women's groups to the presence of salafi/Wahabi groups, which according to them, had taught a different understanding of religion and were not familiar with their religious understanding, and 3) the emergence of competition between the followers of the Teungku Majelis Ta’lim, both in terms of teaching substance and in terms of popularity, which caused disharmony.Keywords : disharmony, majelis, ta’lim, women